Shaping the knowledge society in the 21st century classroom: An HIV/AIDS action research project - Esau, Omar (South African Journal of Higher Education, 2016)
In this paper I set out to describe an HIV/AIDS project that I did with a Grade 6 class in a primary school. This action research project, although conducted in a primary school classroom, has important implications for future teachers who are aware and critical enough to take up social issues and other challenges in their quest to shape the 21st century into a knowledge society. My education project entails the role of the teacher as a researcher and critical change agent in an HIV/AIDS-challenged society. My investigation embodied a variety of concepts drawn from theorists such as Gramsci (1971), Habermas (1972), Freire (1982), Giroux (1988), McLaren (2006) and McNiff (2007). This action research project must, however, not be seen as a blueprint or a recipe for changing one’s classroom practice, but should rather be viewed as an attempt by a teacher who attempted to give a “voice” to, and “empower”, his learners to make meaning of their existence, including himself.